Renal Involvement in Antiphospholipid Syndrome - Turrent-Carriles, Alonso; Herrera-Félix, Juan Pablo; Amigo, Mary-Carmen (Frontiers in Immunology, 2018)
Antiphospholipid syndrome is a complex autoimmune disease, characterized by the presence of vascular thrombosis, obstetric, hematologic, cutaneous, and cardiac manifestations. Renal disease in patients with antiphospholipid syndrome was not recognized in the first descriptions of the disease, but later on, the renal manifestations of the syndrome have been investigated widely. Renal manifestations of antiphospholipid syndrome conform a wide spectrum of diverse renal syndromes. Hypertension is one of the most frequent, but less commonly recognized renal alteration. It can be difficult to control as its origin is renovascular. Renal vascular thrombosis can be arterial or venous. Other alterations are renal infarction and vascular thrombosis in arterial territories. Venous thrombosis can be present in primary and secondary antiphospholipid syndrome; it presents with worsening of previous proteinuria or de novo nephrotic syndrome, hypertension and renal failure. Antiphospholipid syndrome nephropathy is a vascular disease that affects glomerular tuft, interstitial vessels, and peritubular vessels; histopathology characterizes the renal lesions as acute or chronic, the classic finding is thrombotic microangiopathy, that leads to fibrosis, tubule thyroidization, focal cortical atrophy, and glomerular sclerosis. Antiphospholipid syndrome nephropathy can also complicate patients with systemic lupus erythematosus, and there is vast information supporting the worse renal prognosis in this group of patients with the classic histopathologic lesions. Treatment consists of anticoagulation, as for other thrombotic manifestations of antiphospholipid syndrome. There is some evidence of glomerulonephritis as an isolated lesion in patients with antiphospholipid syndrome. The most frequently reported glomerulonephritis is membranous; with some reports suggesting that immunosuppressive treatment may be effective. Patients with end stage renal disease commonly are positive for antiphospholipid antibodies, but it is not clear what is the role of aPL in this setting. Patients with vascular access may have complications in the presence of antibodies so that anticoagulation is recommended. Patients ongoing renal transplant with persistent antiphospholipid antibody positivity may have early and late graft failure.